2008
DOI: 10.2174/1874941000902010001
|View full text |Cite
|
Sign up to set email alerts
|

Nonfatal Bicycle Accident Risk After an Evening of Alcohol Consumption

Abstract: Abstract:Introduction: After an evening of alcohol consumption, blood alcohol concentration (BAC) may reach intoxication levels above legal limits for operating a car or bicycle. In the Netherlands, legal limits for participating in traffic are 0.05% for experienced drivers and 0.02% for novice drivers. The purpose of this study was to determine bicycle accident risk of Dutch students after an evening of alcohol consumption.Methods: A survey was conducted among 800 University and college students in Utrecht, T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…It was found that, on average, almost 62% of the bicyclists in total had alcohol in their blood, and over 40% had a BAC level that is illegal to cycle with in the Netherlands. The average BAC of those who had consumed alcohol was 0.79 g/l, which is close to the estimated BAC of 0.95 g/l reported by Verster et al (2009). Furthermore, it was found that, unsurprisingly, as the night went on the blood alcohol concentration levels measured in bicyclists increased, with a steep increase in BAC between midnight and two AM.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…It was found that, on average, almost 62% of the bicyclists in total had alcohol in their blood, and over 40% had a BAC level that is illegal to cycle with in the Netherlands. The average BAC of those who had consumed alcohol was 0.79 g/l, which is close to the estimated BAC of 0.95 g/l reported by Verster et al (2009). Furthermore, it was found that, unsurprisingly, as the night went on the blood alcohol concentration levels measured in bicyclists increased, with a steep increase in BAC between midnight and two AM.…”
Section: Discussionsupporting
confidence: 80%
“…Despite this law, cycling under the influence of alcohol seems to be common in the Netherlands. For example, Verster et al (2009) found in a survey that most students travel home by bicycle after having consumed alcohol, with an estimated average BAC of 0.95 g/l. However, their estimate was based on a questionnaire study, not on actual measured levels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…That this is far from safe was shown by a survey among 800 Dutch college students (4). For example, the majority of Dutch students report that they do not travel home by car but use a bicycle to get home from the pub.…”
Section: Drivingmentioning
confidence: 99%
“…The relation between alcohol consumption and bicycle accident risk after an evening of alcohol consumption(4) …”
mentioning
confidence: 99%